Increasing student engagement and retention using immersive interfaces virtual worlds, gaming, and simulation - Wankel, Laura A.; Blessinger, Patrick (Cutting-edge technologies in higher education ;, 2012)
Increasing Student Engagement and Retention Using Immersive Interfaces: Virtual Worlds, Gaming, and Simulation uses case studies, surveys, and literature reviews to critically examine how gaming, simulation, and virtualization are being used to improve teamwork and leadership skills in students, create engaging communities of practice, and as experiential learning tools to create inter-cultural, multi-perspective, and global experiences. Chapters include how to increase learner engagement using serious games, using game features for classroom engagement, using client-based peer assessment in multi-role, whole-enterprise simulations, using virtual worlds to develop teacher candidate skills, enhancing leadership skills through virtual simulation, using online video simulation for educational leadership, using augmented reality in education, using open source software in education, using educational robotics laboratories to enhance active learning, and utilizing the virtual learning environment to encourage faculty reflection. This volume will also discuss a framework for deploying and assessing these technologies.